(untitled) (Scientiae Studia, 2009)
Skinner's Radical Behaviorism was strongly influenced by Charles Darwin's evolution theory by means of natural selection. This article aims to discuss the impact of the Darwinism in the development of the radical behaviorist explicative model called selection by consequences. In first place, we examine the importance of the concept of selection in the elucidation of the role of environment. Next, it is argued that Skinnerian interpretation of the origin of behavioral variation provides the means to the defense of the possibility of human creativity. Finally, it is discussed how the renouncement of the creative mind (autonomous man), and the subsequent adoption of variation and selection processes, sheds light on human liberty and dignity in Radical Behaviorism.